Pandemics, payments and fiscal policy: Lessons from four years after the outbreak of Covid-19 - Gerome Wolf (EconPol Forum, 2024)
Existing and well-functioning e-commerce markets and electronic payment systems improve pandemic performance by providing an effective layer of protection against contagious diseases. Covid-19 caused a major reallocation shock to consumer spending. Revolving credit is an effective though underutilized instrument for consumption smoothing during times of economic slack. Generous fiscal support incentivized social distancing stronger and longer and had heterogeneous effects across the wealth distribution.
Keywords: 330